Executive Nurses' Views about Nursing Work Environment: A Qualitative Study - Nilgün Göktepe; Emine Türkmen; Ayda Kebapçı; Selvinaz Albayrak; İbrahim Topçu; Mukaddes Turan Miral; Şehriban Serbest; Duygu Özcan (Association of Nurse Managers, 2020)
INTRODUCTION: INTRODUCTION: Studies showed that the nursing work environment is crucial to improve patient and nurse outcomes in healthcare organizations. Executive nurses have important responsibilities in creating a healthy work environment. AIM: This study was conducted to evaluate executive nurses' views and experiences about nursing work environment at hospitals. METHODS: METHODS: This descriptive and qualitative study was conducted in Istanbul. There were 18 semi-structured and directed interviews with executive nurses who are working in private and public hospitals. Data were collected by tape recorder and were analyzed thematically. RESULTS: RESULTS: There were three main themes: leadership and management practices, nursing staffing and management, and management of relationship and collaboration. It was revealed that the executive nurses' autonomy is low and participation to hospital executive decisions are inadequate, and they provide coordination of non-nursing activities such as housekeeping activities. Executive nurses stated that although there are training and development activities and promotional opportunities in hospitals, the quality, and quantity of nurses are very inadequate. Additionally, they specified that nurses' workload, turnover rate are very high, working conditions are not good, and they had difficulty in generation management. It was also stated that there are problems in cooperation and communication between nurse-physician and nurse-nurse. DISCUSSION AND CONCLUSION: CONCLUSION: Results from individual in-depth interviews, show that executive nurses have many managerial problems in terms of nursing work environment. It is recommended that executive nurses strengthen their communication and collaboration with their teams, managers and policy makers in order to implement healthy workplace standards. Keywords: Hospital, nursing work environment, executive nurse.